The great Indian epidemic of superficial dermatophytosis: An appraisal - Verma, Shyam; Madhu, R (Indian journal of dermatology, 2017)
While environmental factors, erratic use of topical and oral antifungal agents, increased prevalence of Trichophyton mentagrophytes infections causing inflammatory lesions and probably a growing resistance to antifungal agents may play an important role, one of the most formidable enemies that we have encountered in the recent times is the irrational fixed drug combination (FDC) creams containing a steroid, antifungal, and antibacterial with three to five molecules in the product. An important article highlighting the conclusions of an expert panel meeting on topical treatment of superficial dermatophytoses written after reviewing numerous meta-analyses arrived at some conclusions supporting these combination creams. The authors of this seminal article concluded that adding topical corticosteroid to a topical antifungal agent in the beginning of the therapy can mitigate bothersome inflammation, reduce secondary colonisation with bacteria and enhance the efficacy of the antifungal drug. All the five authors practice in European countries where laws controlling the production and sales of drugs are stringent and are implemented. [...]this publication though comprehensive and erudite is not entirely relevant in the Indian context. The authors have specifically mentioned that the corticosteroid may be added in the initial part of the treatment and improper use of the combination creams may lead to both failure of treatment and adverse reactions. [1],[11] This speaks volumes about the inadequate understanding of the drug control authorities of India who grant permissions to companies manufacturing them. [...]they are used erratically, often only for symptom control and that too without any instructions or supervision. Pande S...